Indian documentary film and filmmakers : independence in practice - Kishore, Shweta (Edinburgh University Press, 2018)
Based on detailed onsite observation of documentary production, circulation practices and the analysis of film texts, this book identifies independence as a'tactical practice', contesting the normative definitions and functions assigned to culture, cultural production and producers in a neoliberal economic system.
Keywords: Documentary films -- Production and direction -- India.; Documentary films -- India -- History and criticism.; Motion picture producers and directors -- India.; Documentaires -- Production et réalisation -- Inde.; Producteurs et réalisateurs de cinéma -- Inde.; Documentaires -- Inde -- Histoire et critique.; PERFORMING ARTS -- Film & Video -- Direction & Production.; Documentary films; Documentary films -- Production and direction; Motion picture producers and directors; India; Criticism, interpretation, etc.